Researching women's lives: Issues of epistemology from the feminist perspective - Yusof, Rohana @ Norliza (Penerbit Universiti Utara Malaysia, 2005)
Over the last two decades feminist inquiries have raised fundamental challenges to the ways social science has analyzed women, men, and social life. From the beginning, issues about method, methodology, and epistemology have been intertwined with discussion of how best to correct the partial and distorted accounts in the traditional analyses. Is there a distinctive feminist method of inquiry? On what grounds would one defend the assumptions and procedures of feminist researchers? Questions such as these have generated important controversies within feminist theory and politics, as well as curiosity and anticipation in the traditional discourses (Harding, 1987). Brannen (1994) has pointed out three things in particular that are leading feminists to reconsider their position on method: (i) There is the need to acknowledge that the qualitative techniques they have tended to favour are not in and of themselves specific to feminism.(ii) Indeed, they are all an integral part of social science research and have their own histories of development and change outside and (iii) Independent of feminism. Feminist may have appropriated these techniques, but they did not create them. They have also modified them, although they are not alone in doing so.(iv) In addition, a number of researchers have recently drawn attention to the ways in which the polarization of quantitative versus qualitative impoverished research, and there have been calls for the use of multiple method to be used in a complementary rather than a competitive way.